1975
DOI: 10.4039/ent107361-4
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR CIS-11-HEXADECEN-1-OL ACETATE AS A MAJOR COMPONENT OF THE SEX PHEROMONE OF THE BERTHA ARMYWORM, MAMESTRA CONFIGURATA (LEPIDOPTERA: NOCTUIDAE)

Abstract: A potent sex pheromone produced by female bertha army worm moths was isolated. A 16 carbon, unsaturated, alkenol acetate was indicated from chemical degradative and GLC retention data. The location and configuration of the double bond was determined from the antennal responses (EAG) of male moths to a series of cis and trans mono-unsaturated alken-1-ol acetates; cis-11-hexadecen-1-ol acetate elicited the greatest EAG response. GLC retention times of the purified insect sex pheromone corresponded exactly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…He reported that in old females calling was initiated as early as the 2nd h of the scotophase in a few females and the duration of the calling period was about 280 min. Chisholm et al (1975) had found that calling occurred during the last half of the scotophase in M. configurata. Thus, almost all of the calling takes place during the last two-thirds of the scotophase at all ages in this species.…”
Section: Discussionmentioning
confidence: 99%
“…He reported that in old females calling was initiated as early as the 2nd h of the scotophase in a few females and the duration of the calling period was about 280 min. Chisholm et al (1975) had found that calling occurred during the last half of the scotophase in M. configurata. Thus, almost all of the calling takes place during the last two-thirds of the scotophase at all ages in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Mamestra configurata was trapped with the two-component A. orbis pheromone blend, again in one test. Z11216:Ac is the major component of the M. configurata pheromone (Chisholm et al 1975) but there are no reports that in this species Z7214:Ac is part of the pheromone or is a co-attractant with Z11216:Ac. These nontarget species of moths were not consistently captured in our experiments, and captures varied in size by location and year.…”
Section: Discussionmentioning
confidence: 98%
“…Male antennal responses to C,, to C,, saturated, Z-and E-monounsaturated (isomers beyond C-3), and C,, diunsaturated acetates, alcohols, and aldehydes were measured by EAG (Chisholm et al 1975) using 1-pg test samples on filter paper discs. Each compound was tested at least twice.…”
Section: Methodsmentioning
confidence: 99%